1999
DOI: 10.1111/1469-7610.00540
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health in International Adoptees as Teenagers and Young Adults. An Epidemiological Study

Abstract: Sweden has now around 38,000 individuals who have been adopted from other countries. Most often they are transracially adopted and have a different appearance from their new parents--"visible" adoptions. This study was made to explore the mental health of a teenager/young adult group that arrived with their families in the southernmost county of Sweden between 1970 and 1977. They were placed through the largest Swedish adoption agency at that time. One hundred and forty-seven families and their 211 adopted chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
52
2
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(62 citation statements)
references
References 14 publications
4
52
2
2
Order By: Relevance
“…Behaviorally, PI children adopted as sibling groups have higher ages at adoption but have lower or similar rates of behavior problems compared to single adoptees (Boer, Versluis-den Bieman, & Verhulst, 1994;Van den Oord, Boomsma, & Verhulst, 1994), and similar patterns are found for domestic adoptees (Erich & Leung, 2002;Hegar, 2005). This finding suggests a protective effect of having a sibling because older age at adoption is generally related to more, not fewer, behavior problems (Cederblad et al, 1999;Gunnar et al, 2007;Rutter et al, 2010).…”
Section: Siblingsmentioning
confidence: 90%
See 1 more Smart Citation
“…Behaviorally, PI children adopted as sibling groups have higher ages at adoption but have lower or similar rates of behavior problems compared to single adoptees (Boer, Versluis-den Bieman, & Verhulst, 1994;Van den Oord, Boomsma, & Verhulst, 1994), and similar patterns are found for domestic adoptees (Erich & Leung, 2002;Hegar, 2005). This finding suggests a protective effect of having a sibling because older age at adoption is generally related to more, not fewer, behavior problems (Cederblad et al, 1999;Gunnar et al, 2007;Rutter et al, 2010).…”
Section: Siblingsmentioning
confidence: 90%
“…Indirectly, several studies that use parent-reported measures of children's social problems, which are likely related to friendship quality, find that PI children have more reported social problems (Hoksbergen, Rijk, Van Dijkum, & Laak, 2004;Stams, Juffer, Rispens, & Hoksbergen, 2000;Verhulst, Althaus, & Versluis-Den Bieman, 1990) and disinhibited social behaviors (Bruce, et al, 2009) than non-PI children. Also, later adopted PI children (> 7-24 months at adoption) tend to have more parent-reported social problems than earlier adoptees (Cederblad, et al, 1999;Gunnar et al, 2007;Hawk & McCall, in press;Julian, 2010). These studies suggest that more exposure to institutions with deficient social-emotional relationships, few contingent-responsive interactions, and few opportunities to learn appropriate social skills, is related to more social and friendship problems.…”
Section: Friendsmentioning
confidence: 99%
“…Furthermore, many international adoptees experienced early maltreatment (Gunnar et al 2000;Verhulst et al 1992), but they were subsequently taken out of their problematic environment in childhood and raised in enriched circumstances. Previous studies in internationally adopted samples demonstrated effects of early adversities on mental health problems in childhood, adolescence or adulthood (e.g., Cederblad et al 1999;Fensbo 2004;Fisher et al 1997;Hoksbergen 1997;Juffer and Van IJzendoorn 2005;Marcovitch et al 1997;Verhulst et al 1992). These internationally adopted samplesproblems.…”
mentioning
confidence: 88%
“…On the one hand, our results seem to confirm several studies, which found that early adversities have long-term effects on the level of psychiatric problems (e.g., Keiley et al 2001;Lansford et al 2002;Trickett and McBride-Chang 1995;Tyler 2002). For example, Cederblad et al (1999), studying mainly adoptees from Korea, India, and Colombia, showed an association between duration of care in an orphanage or foster home and mental health problems. Hoksbergen (1997) found that there was an increased risk of disruption and residential care in children adopted from Thailand, who had lived in an orphanage or had experienced several changes of caretaking places.…”
Section: Trajectories Of Psychiatric Problems In Maltreated Childrenmentioning
confidence: 99%
“…This feeling of loss, in turn, has been found to be associated with greater depressive symptoms and lower self-worth among domestically and internationally adopted preadolescents (Smith & Brodzinsky, 2002). Similarly, Cederblad, Höök, Irhammer, and Mercke (1999) reported that uncertainty about one's ethnic identity and perceived discrimination are related to greater psychological distress and lower self-esteem among international adoptees. Adoptive parents, most of whom are White and of European descent, likewise are confronted with decisions about when and how to appropriately acknowledge and address ethnic and racial differences with their children without disrupting family bonds.…”
mentioning
confidence: 95%